Transatlantic Anxieties: Democracy and Diversity in Nineteenth-Century Discourse. Issue 2 (October 2019) - Bateman, David A.
Abstract : This article reconstructs a set of widely disseminated nineteenth-century ideas about the relationship between diversity and democracy and details how these informed state-building and political action. An emerging argument in nineteenth-century discourse held that representative governments in diverse societies would degenerate into anarchy without "amalgamation, " extermination, expulsion, or enslavement: Only in societies where there was sympathy across the entire community, constantly renewed through intercourse among social equals, could free institutions be sustained. This argument gave support for state-builders to regulate diversity either through an imperial politics of "moving people" or by interposing the state in intimate encounters of sexual and social intercourse. The intimate and imperial dimensions of state-building were thereby conceptually linked. This account helps explain important features of nineteenth-century politics, including the frequent criticism of abolitionists that by supporting racial civic or political equality they were encouraging "racial amalgamation." In responding to this charge, American antislavery discourse contributed to a distinction between political and social equality that would fundamentally shape state-building after the Civil War. The article shows scholars of American political development how our accounts might be revised by situating debates and developments within a transnational perspective.